Асоцијација за демократски инцијативи – АДИ Гостивар; Организација на жени на град Скопје - Алберт Муслиу,; Томка Дилевска, (Ревија за социјална политика/Journal of Social Policy, 2009)
Although the concept of anti-discrimination is not a substitution of the anomalies in society that are created as a product of long-term discrimination and exclusion of individuals depending on their ethnic, gender, religious and other belongings and specifics, the adoption of a legal framework for combating discrimination should provide the results of former long-term discrimination will not deepen further, as well as to prevent new cases of discrimination in the future